From polybenzimidazoles to polybenzimidazoliums and polybenzimidazolides - Aili, David; Yang, Jingshuai; Jankova, Katja; Henkensmeier, Dirk; Li, Qingfeng (ROYAL SOC CHEMISTRY, 2020)
Polybenzimidazoles represent a large family of high-performance polymers containing benzimidazole groups as part of the structural repeat unit. New application areas in electrochemical cells and separation processes have emerged during the last two decades, which has been a major driver for the tremendous development of new polybenzimidazole chemistries and materials in recent years. This comprehensive treatise is devoted to an investigation of the structural scope of polybenzimidazole derivatives, polybenzimidazole modifications and the acid-base behavior of the resulting materials. Advantages and limitations of different synthetic procedures and pathways are analyzed, with focus on homogeneous solution polymerization. The discussion extends to solution properties and the challenges that are faced in connection to molecular weight determination and processing. Methods for polybenzimidazole grafting or crosslinking, in particular by N-coupling, are reviewed and successful polymer blend strategies are identified. The amphoteric nature of benzimidazole groups further enriches the chemistry of polybenzimidazoles, as cationic or anionic ionenes are obtained depending on the pH. In the presence of protic acids, such as phosphoric acid, cationic ionenes in the form of protic polybenzimidazoliums are obtained, which dramatically changes the physicochemical properties of the material. Cationic ionenes are also derived by completeN-alkylation of a polybenzimidazole to the corresponding poly(dialkyl benzimidazolium), which has been intensively explored recently as a new direction in the field of anion exchange membranes. In the higher end of the pH scale in aqueous hydroxide solutions, anionic ionenes in the form of polybenzimidazolides are obtained as a result of deprotonation of the benzimidazole groups. The ionization of the polymer results in dramatically changed physicochemical properties as compared to the pristine material, which is described and discussed. From a technological point of view, performance and stability targets continue to motivate further research and development of new polybenzimidazole chemistries and energy materials. The overall aim of this review is therefore to identify challenges and opportunities in this area from synthetic chemistry and materials science perspectives to serve as a solid basis for further development prospects.